Analisis Tingkat Risiko Virus Komputer Menggunakan Metode Simple Additive Weighting SAW - Ade Kurnia Kurnia Ramzani (Jurnal Informatika, 2026)
The rapid advancement of information technology has led to increased computer and network usage across various activities; however, it has also heightened the risk of cyberattacks, particularly those involving computer viruses or malware. Since each type of malware possesses distinct characteristics and varying levels of danger, a method is required to objectively assess the risk level of each virus. This study aims to analyze computer virus risk levels using the Simple Additive Weighting (SAW) method. The alternatives evaluated in this study include Trojans, Worms, Spyware, Ransomware, and Adware. The criteria employed encompass the rate of spread, system damage, data theft capability, detection difficulty, and impact on system performance. The SAW method was applied through a process involving criteria weighting, decision matrix normalization, preference value calculation, and alternative ranking. The results indicate that Ransomware achieved the highest preference value (0.96), thereby ranking first as the virus with the highest risk level. This was followed by Trojans (0.81), Worms (0.74), Spyware (0.71), and Adware (0.48). These findings demonstrate that the SAW method facilitates a systematic and objective analysis of computer virus risk levels, serving as a basis for prioritizing responses to malware threats